2008
DOI: 10.1111/j.1464-410x.2008.07597.x
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic renal function after unilateral pyeloplasty in children: a systematic review

Abstract: OBJECTIVE To systematically review previous reports and thus determine the functional outcome after pyeloplasty in children with unilateral hydronephrosis due to pelvi‐ureteric junction obstruction, and the possible variables that could affect it. METHODS We searched Medline/PubMed, Embase, and Web of Science for articles in English published from 1966 to 2007, using both ‘medical subject headings’ and ‘free text’ protocols. Abstracts, full texts, and bibliographies of pertinent papers were reviewed to select … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 50 publications
(193 reference statements)
3
27
1
4
Order By: Relevance
“…Although the goal of pyeloplasty is primarily to preserve renal function and provide symptomatic relief, recoverability of renal function is a matter of debate and has been a subject of extensive literature research, especially in the pediatric population [1,3,6,9,10,11]. We showed that the overall DRF and SKGFR were significantly improved after relief of obstruction.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although the goal of pyeloplasty is primarily to preserve renal function and provide symptomatic relief, recoverability of renal function is a matter of debate and has been a subject of extensive literature research, especially in the pediatric population [1,3,6,9,10,11]. We showed that the overall DRF and SKGFR were significantly improved after relief of obstruction.…”
Section: Discussionmentioning
confidence: 59%
“…However, our report has several limitations in that it is retrospective and, in addition, we estimated the recoverability of renal function based on diuretic scintigraphy whose accuracy has been questioned [2,9]. Although postoperative diuretic scintigraphy has been performed at a median follow-up of 11 months, not all patients underwent scintigraphy at the same intervals.…”
Section: Discussionmentioning
confidence: 99%
“…15 There are several limitations to our study. Our data were obtained retrospectively, which limited the type of information we could collect and the types of statistical analyses we could perform.…”
Section: Discussionmentioning
confidence: 94%
“…14 A systematic review in this area by Castagnetti et al (2008) concluded that symptomatic patients diagnosed postnatally, and those with moderate rather than severely compromised preoperative function seem to have the greatest chance of functional improvement after surgery. 15 There are several limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
“…The ureteropelvic junction is the most common site of congenital urinary obstruction above the level of the bladder. 19,20 The resulting hydronephrosis may be unilateral or bilateral. In adults, pulsed Doppler sonography was used for the diagnosis of lower pole arteries, which cross the ureteropelvic junction and are possibly the reason for hydronephrosis.…”
Section: Obstructive Uropathiesmentioning
confidence: 99%